KINERJA KARYAWAN KITCHEN PADA DEPARTEMEN CREW OUTLET RICHEESE FACTORY PEKANBARU - M. Fauzi Putra; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Richeese Factory Pekanbaru is a fast food restaurant founded by PT. Indonesian Culinary PT. Culinary Indonesia is one of the subsidiaries of the Nabati Group. Richeese Factory is a restaurant that provides self service by customers and also a restaurant that prioritizes excellent service for customer satisfaction. The purpose of this study was to determine the performance of kitchen employees at the Crew Outlet Richeese Factory Pekanbaru. This study uses a quantitative method with a descriptive approach to identify the problems that exist in the Richeese Factory Pekanbaru. Respondents in this study amounted to 5 people, while the data collection techniques in this study used observation, interviews, and documentation. The results showed that the Kitchen Employee Performance at the Crew Outlet Department of Richeese Factory Pekanbaru was not good. In the implementation of Kitchen Employee Performance, there is a lack of employee discipline and employee understanding of the work instructions at Richeese Factory Pekanbaru.  Keywords: Performance, Employees, Kitchen, Restaurant